Synthesis of Amorphous Aluminosilicates from Bintan’s Red Mud as Alumina Source - Futri Wulandari; Eka Putra Ramdhani; Yatim Lailun Ni’mah; Ahmad Anwarud Dawam; Didik Prasetyoko (Indonesian Journal of Chemistry, 2018)
Red mud is a generated by-product in alumina production from bauxite ore. In this study, Bintan’s red mud has been used as alumina and silica source to synthesize amorphous mesoporous aluminosilicates material. Alkali fusion method with a NaOH/red mud ratio 0.8; 1.0; 1.2; 1.4 and 1.5 followed by hydrolysis method was used to extract dissolved alumina and silica from red mud. Synthesis of amorphous aluminosilicates by hydrothermal method was conducted at 80 °C for 24 h. Cetyltrimethylammonium bromide (CTABr) was added as the structure directing agent. Aluminosilicate products were characterized using FTIR spectroscopy (Fourier Transform Infra-Red Spectroscopy), XRD (X-ray Diffraction), SEM (Scanning Electron Microscopy), and nitrogen adsorption-desorption. XRD and SEM result shows that the product was amorphous with low uniformity in terms of surface morphology and particle size. Nitrogen adsorption-desorption profile shows that all aluminosilicates products has a meso pore structure, confirmed by the highest pore distribution at 3.05–17.70 nm. The highest surface area and pore volume were obtained in ASM 0.8 (NaOH/red mud ratio = 0.8) i.e. 177.97 m2/g and 1.09 cm3/g, respectively.